A novel nonsense variant in the NFE2L1 transcription factor in a patient with developmental delay, hypotonia, genital anomalies, and failure to thrive. Issue 4 (7th February 2022) - Wang, Julia M.; Ho, Daniel V.; Kritzer, Amy; Chan, Jefferson Y.
Abstract: The NFE2L1 transcription factor (also known as Nrf1 for nuclear factor erythroid 2‐related factor‐1) is a broadly expressed basic leucine zipper protein that performs a critical role in the cellular stress response pathway. Here, we identified a heterozygous nonsense mutation located in the last exon of the gene that terminates translation prematurely, resulting in the production of a truncated peptide devoid of the carboxyl‐terminal region containing the DNA‐binding and leucine‐zipper dimerization interface of the protein. Variant derivatives were well expressed in vitro, and they inhibited the transactivation function of wild‐type proteins in luciferase reporter assays. Our studies suggest that this dominant‐negative effect of truncated variants is through the formation of inactive heterodimers with wild‐type proteins preventing the expression of its target genes. These findings suggest the potential role of diminished NFE2L1 function as an explanation for the developmental delay, hypotonia, hypospadias, bifid scrotum, and failure to thrive observed in the patient.